A PRECISION MEDICINE TEST REDUCED UNNECESSARY DOWNSTREAM EVALUATIONS IN ELDERLY WITH SUSPECTED CORONARY DISEASE. (16th November 2018) - Ladapo, J; Stradford, L; Cool, C; Monane, M; Lansky, A
Abstract: The objective of this study was to compare healthcare utilization and clinical outcomes among patients with suspected coronary artery disease (CAD) using a blood-based age/sex/gene expression score (ASGES) versus conventional cardiac functional or anatomical testing. Using administrative claims records from July 2015 to April 2017, we identified a cohort of Medicare Advantage patients evaluated with ASGES and a propensity-matched control cohort evaluated with conventional cardiac testing on the index date. Data on utilization of noninvasive/invasive cardiac testing and major adverse cardiac events (MACE) were collected in the 6 month period after the index date. This analysis yielded 1421 patients (63% female, median age 72 years old), including 306 patients evaluated with ASGES testing and 1115 control patients evaluated with conventional cardiac testing. At 6 months after the index date, the incidence of cardiovascular-related resource utilization, including office visits, emergency room visits, and inpatient admissions, was 3.6% among ASGES patients versus 7.4% among control patients (p=0.026). The incidence of invasive coronary angiography was 2.6% among ASGES patients vs. 8.6% among control patients (p<0.0001). The incidence of MACE at 6 months was not significantly different between ASGES and control patients (0.0% vs. 0.6%, p=NS). In conclusion, this claims data analysis demonstrated the comparative clinical effectiveness of the ASGES in this elderly population: elderly patients with symptoms suggestive of obstructive coronary artery disease evaluated with ASGES testing had lower rates of invasive procedures and cardiovascular-related encounters with no difference in safety outcomes versus elderly patients undergoing conventional functional or anatomical cardiac testing.